Treinamento de habilidades sociais para pais de crianças com queixas escolares - Barros, Sibely Karina da Silva Nogueira de (Universidade Federal de São Carlos, 2008)
The relation between learning disabilities and school subjects can be easily seen by lay people as well as by professionals and students in the area. Besides this relation, literature has shown that a child s family environment, mainly the parents, play an important role in either strengthening or weakening social skills and study habits. This research was aimed at testing the effects of a training program in educational social skills for parents on their children s school performance. The present study involved 15 parents whose children, 1st 8th graders from public and private schools, were denominated by their children as having scholl problems. Parents were divided randomly in an Experimental Group (N=8) and a nonequivalent Control Group (N=7). The training program in social skills for parents was structured in thirteen sessions which took place once a week, each lasting approximately 120 minutes, in a Psychology Clinic located in a town in the state of São Paulo. Instruments of direct and indirect verification were used to evaluate behavior: filming, Checklist for parents and Test of School Performance ( Teste de Desempenho Escolar , TDE-Stein, 1994). The study was divided into four stages: (a) initial evaluation; (b) intervention; (c) final evaluation; and (d) follow-up after six months. Descriptive statistics was used to present data and content analysis was used to interpret the results, especially with regards to its clinical relevance and social acceptance. Results suggest that there has been an increase in social skills reported by the parents and an improvement in their children s school performance after intervention. Parent s social skills seem to have contributed positively to the reduction of their children s school problems. Parents who are highly involved in their children s lives can behave in desirable manner with regards to helping in school chores, as well as serving as good models in social and academic situations, which in turn help improve children s social and academic skills. The training program in social skills for parents has proved to be an effective method to solve interaction problems, especially those related to the school problems complaints on the school performance and/or related to the social interactions in classroom. These results also demonstrate the importance of positive involvement from both parents on their children s social-emotional development and school performance and the necessity of training programs for parents.
Keywords: Aprendizagem; Habilidades sociais; Programa de intervenção; Treinamento de pais; Dificuldade de aprendizagem; Educação especial; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL